Peningkatan Hasil Belajar Menggunakan Model Kooperatif Tipe Two Stay Two Stray di Sekolah Dasar - Husnathul Khulfah Rezki; Yesi Anita (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2023)
This research is motivated by low student achievement. The aim of the study was to describe the increase in student learning outcomes in integrated thematic learning with the Two Stay Two Stray Cooperative Model in Class V SD Negeri 01 Bandar Buat. This type of research is classroom action research with a qualitative approach and a quantitative approach with four stages, namely planning, implementing, observing, and reflecting. Conducted in two cycles, cycle I consisted of 2 meetings, and Cycle II consisted of 1 meeting. The research subjects were teachers and fifth-grade students at SDN 01 Bandar Buat, totalling 27 people. The results showed that the observation of lesson plans for the cycle I averaged 83.32% (B) and increased in cycle II with a percentage of 94.44% (SB), in cycle I teacher activity an average of 86.10% (B) increased in cycle II with a percentage of 94.44% (SB), in the activity of students in cycle I an average of 86.10% (B) increased in cycle II with a percentage of 94.44% (SB) and student learning outcomes in cycle I averaged average 77.82 (C) increased in cycle II 91.72 (B). Thus, it can be concluded that the TSTS-type cooperative model can improve student learning outcomes in integrated thematic learning in class V SD Negeri 01 Bandar Buat Padang City.